Peran Kreativitas Guru dan Ketersediaan Laboratorium dalam Pelaksanaan Praktikum Kimia untuk Meningkatkan Kemampuan Berpikir Kritis Siswa di SMA - ; Kartyka Nababan (Syntax Idea)
The study aims to explore the role of teacher creativity and the availability of laboratories in performing chemical experiments to enhance the students' critical thinking abilities in high schools. Research methods used include the study of literature by collecting data from sources that are relevant to the topic and analysing it using descriptive and qualitative methods. Research shows that teacher creativity and the availability of laboratory facilities play a crucial role in the institution of effective chemical programs in high school, which aim to enhance students' critical thinking abilities. The faculty's ability to devise practicality and teach chemical concepts helps students better understand the material and train their critical thinking skills. In addition, adequate laboratory facilities enable students to experiment directly and experience practical chemical concepts, which support their understanding of the material.